2018
DOI: 10.1016/j.ergon.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, precision and reliability in anthropometric surveys for ergonomics purposes in adult working populations: A literature review

Abstract: Anthropometric surveys are the most common method of gathering human morphometric data, used to design clothing, products and workspaces. The aim of this paper was to assess how current peer reviewed literature addresses the accuracy, reliability and precision regarding manual anthropometric surveys applied to adult working populations in the field of ergonomics. A literature review was performed in two electronic databases for finding relevant papers. A total of 312 papers were reviewed, of which 79 met the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 101 publications
0
22
0
1
Order By: Relevance
“…Additionally, the 1995 study only used two observers that inter-changed functions between them, which could have induced error. The lack of a third observer could have made it more difficult to address any postural deviations of the participants while being measured [29].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the 1995 study only used two observers that inter-changed functions between them, which could have induced error. The lack of a third observer could have made it more difficult to address any postural deviations of the participants while being measured [29].…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of correct postural alignment in activities of daily life relies largely on accurate sensing of postural alignment and the subsequent repositioning [26][27][28][29] of postural alignment. Literature reports on numerous disciplines' interest in the field of accuracy studies 34 , and results influencing practices and development of professions such as human factors in aviation 35 , sport performance ergonomics and management 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that anthropometric protocols are generally defined in broad terms, which may lead to misinterpretation of fine measurement technique. Results of a recent review indicated that the accuracy, reliability and precision issues regarding manual anthropometric surveys are poorly addressed in the ergonomics literature (Viviani et al, 2018). It was shown that only 27 of the 79 reviewed papers mentioned at least one of the terms and none of the papers evaluated all of the terms.…”
Section: Comparison Of Methodsmentioning
confidence: 99%
“…Only one paper mentioned and assessed precision and reliability of the measurement procedure, while none of the publications evaluated accuracy. It seems that the most difficult part of the issue is to establish the 'true value' of measurements (Viviani et al 2018). In this regard, the International Society for the Advancement of Kinanthropometry (ISAK) (http:// www.isak.global/) is an example which not only defines protocols precisely, but also conducts practical courses that quantify intra-and inter-measurer errors and offer 4 levels of measurement certificates.…”
Section: Comparison Of Methodsmentioning
confidence: 99%